2022
DOI: 10.3390/pharmaceutics14102172
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Phenomena of Nanoliposomes by Live Imaging of Primary Cultures of Cortical Neurons

Abstract: Soft nanoparticles, and in particular, nanoliposomes (NL), have attracted increasing interest for their use in food, nutraceuticals, and in particular, in pharmaceutics for drug delivery. Recent data using salmon lecithin NL suggest that these NL, rich in omega-3 (n-3) fatty acids, can improve the bioavailability and transport of molecules through the blood brain barrier (BBB) to target the brain for the prevention and treatment of neurodegenerative diseases. The objective of this study was to characterize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…We previously showed that NL particles can be internalized by neurons through a process resembling endocytosis [ 13 ]. We would thus propose that upon exposure to neurons, the curcumin-loaded NL formulations were internalized, allowing direct access to curcumin intracellularly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that NL particles can be internalized by neurons through a process resembling endocytosis [ 13 ]. We would thus propose that upon exposure to neurons, the curcumin-loaded NL formulations were internalized, allowing direct access to curcumin intracellularly.…”
Section: Resultsmentioning
confidence: 99%
“…Lecithin was extracted and purified from the heads of Salmo salar (Atlantic salmon) using a low-temperature enzymatic hydrolysis without any organic solvents [ 13 ]. Chloroform, methanol, and Dulbecco’s phosphate-buffered saline (DPBS) were purchased from Thermo Fisher Scientific (Ref: 14190144, Gibco, Massy, France).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive outcomes highlight the efficiency of lipid nanoparticles and nanostructured lipid carriers to target the brain and protect against ischemic stroke [ 161 , 162 , 163 ]. The intranasal route of PUFAs or other drug delivery via lipid nanoparticles is also very promising, allowing the drug to directly reach the brain by bypassing the blood–brain barrier, a structure that restricts the passage of therapeutic agents and limits the efficacity of the delivery [ 164 , 165 , 166 , 167 ].…”
Section: Lipids and Ischemic Strokementioning
confidence: 99%
“…Liposomes, first introduced in 1965, are rounded vesicles composed of either single or multiple lipid bilayers with an aqueous center [ [48] , [49] , [50] ]. These vesicles can spontaneously form when amphiphilic lipids, such as phospholipids, are dispersed in water and closely resemble our cellular membranes [ 51 , 52 ]. This similarity serves as an immense advantage for drug delivery in terms of biocompatibility and biodegradation.…”
Section: Introductionmentioning
confidence: 99%